Controlling the synthesis parameter during fe(OH)2 precipitation for goethite formation - Noraishah Binti Mohamed Noor (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
Iron oxide were synthesized goethite free of magnetic impurities with different crystal sizes in different molar ratio and mixing time through the reverse precipitation of FeSO47H2O and NaOH. Mostly goethite mineral present in cold environment naturally but in this thesis we try to create goethite under a room temperature (35oC ~). Final products were characterised by several testing like Scanning Electron Microscopy to find the morphology and EDS, and X-ray Diffraction to find the phase and crystalline.